The Antidepressant-Like Effects of a Clinically Relevant Dose of Ketamine Are Accompanied by Biphasic Alterations in Working Memory in the Wistar Kyoto Rat Model of Depression - McDonnell, Conor W.; Dunphy-Doherty, Fionn; Rouine, Jennifer; Bianchi, Massimiliano; Upton, Neil; Sokolowska, Ewa; Prenderville, Jack A. (Frontiers in Psychiatry, 2021)
Major depressive disorder (MDD) is the leading cause of disability worldwide. The majority of antidepressant drugs require several weeks or months of treatment to demonstrate efficacy and a subset of patients are resistant to such interventions. Ketamine demonstrates rapid and long-lasting antidepressant effects in treatment resistant patients; however, side effects may limit its widespread clinical utility. The pharmaceutical industry is engaged in developing novel rapid-acting antidepressant drugs and the establishment of clinically relevant assays are needed to advance this process. Wistar Kyoto (WKY) rats are a valuable model of many of the characteristics of MDD and their resistance to selective serotonin reuptake inhibitors (SSRIs) in several behavioural paradigms emulates treatment resistance in clinical populations. Here, we confirmed the depressive-like phenotype of WKY rats in comparison to Sprague Dawley rats, characterised by increased immobility in the forced swim test, decreased locomotor activity and entries to the centre in the open field test, anhedonia in the female urine sniffing test and working memory deficits in the delayed non-match to position task. Single subcutaneous administration of 5 mg/kg ketamine in WKY rats mirrored the plasma exposure produced by the antidepressant dose in the clinic and rescued depressive-like behaviours. The same dose induced transient side effects, including decreased locomotor activity and reduced positive affect-associated vocalisations. Furthermore, ketamine acutely impaired working memory but induced pro-cognitive effects at a later time point. These data confirm the WKY rat as a preclinical model of depression. Ketamine’s efficacy in recovering this depressive-like phenotype while inducing transient dissociative-like effects supports this as a translational model suitable for investigating novel antidepressant drugs.